2020
DOI: 10.3390/biom10121637
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and Intracellular Membrane Trafficking Subversion by Pathogenic Yersinia Species

Abstract: Yersinia pseudotuberculosis, Y. enterocolitica and Y. pestis are pathogenic bacteria capable of causing disease in humans by growing extracellularly in lymph nodes and during systemic infections. While the capacity of these bacteria to invade, replicate, and survive within host cells has been known for long, it is only in recent years that their intracellular stages have been explored in more detail. Current evidence suggests that pathogenic Yersinia are capable of activating autophagy in both phagocytic and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 59 publications
(87 reference statements)
0
9
0
Order By: Relevance
“…Both Yersinia and Listeria have been shown to activate autophagic mechanisms, and it was suggested that those mechanisms facilitate the destruction of the bacteria [44,45]. Activation of MLKL was also reported to facilitate autophagy [46].…”
Section: Mlkl Ubiquitination Also Facilitates the Destruction Of Some Other Intracellular Bacteriamentioning
confidence: 99%
“…Both Yersinia and Listeria have been shown to activate autophagic mechanisms, and it was suggested that those mechanisms facilitate the destruction of the bacteria [44,45]. Activation of MLKL was also reported to facilitate autophagy [46].…”
Section: Mlkl Ubiquitination Also Facilitates the Destruction Of Some Other Intracellular Bacteriamentioning
confidence: 99%
“…If decoration by LC3B-positive membranes is only delayed to late time points of infection and if this also leads to lysosomal degradation of engulfed bacteria deserves further investigation. For several Yersinia strains it was reported that degradation by fusion with lysosomes is inhibited and Yersinia is able to replicate in a non-acidic autophagosome (Connor et al, 2018; Lemarignier & Pizarro-Cerda, 2020; Moreau et al, 2010; Straley & Harmon, 1984). Further investigations assessing acidification of LC3B-positive compartments and interfering with autophagosome formation using Lysotracker, siRNA approaches, and autophagy inhibitors such as 3-MA in combination with replication assays could help to understand the host-pathogen interactions in SPA in more detail.…”
Section: Discussionmentioning
confidence: 99%
“…Although macrophages are important phagocytic cells that have the ability to kill bacteria, there is evidence that Y. ruckeri survives and multiplies intracellularly in these cells (Ryckaert et al, 2010;Welch & Wiens, 2005). Other pathogenic Yersinia species, such as Y. enterocolitica and Y pseudotuberculosis, have been shown to survive in macrophages (Lemarignier & Pizarro-Cerda, 2020). Similarly to Y. ruckeri, these human pathogens invade through the intestine before spreading to other tissues.…”
Section: Discussionmentioning
confidence: 99%